Антиквар: [роман] / А. А. Бушков - Бушков Александр Александрович (ОЛМА Медиа Групп, 2009)
Экземпляры: аб. (2009) / Инвентарный номер: 52712 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 94 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44